2018
DOI: 10.1590/rbz4720170077
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and export of nutrients in cactus pear cladodes (Opuntia ficus-indica) under different managements in the Brazilian Semiarid

Abstract: The present study evaluated the accumulation and export of nutrients in cactus pear (Opuntia ficus-indica) cv. Gigante, fertilized with combinations of nitrogen (10, 70, 100, 130, and 190 kg ha −1 year −1 N) and phosphorus (10, 70, 100, 130, and 190 kg ha −1 year −1 P 2 O 5) under annual and biennial harvests, in Quixadá and Tejuçuoca, using a split-plot randomized block design with four replications. In Quixadá, under annual and biennial harvests, the following orders of accumulation of macronutrients (in kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Differences in chemical composition between cactus varieties during rainy and dry seasons was reported by Alves et al (2016Alves et al ( , 2017a. In the rainy season, plant growth and development leads to nutrient accumulation across plant organs (LOPES et al, 2018). Water deficit negatively affects cell multiplication and elongation, resulting in reduced photosynthesis and respiration, as well as transpiration and evaporation (TAIZ et al, 2017).…”
Section: Resultsmentioning
confidence: 94%
“…Differences in chemical composition between cactus varieties during rainy and dry seasons was reported by Alves et al (2016Alves et al ( , 2017a. In the rainy season, plant growth and development leads to nutrient accumulation across plant organs (LOPES et al, 2018). Water deficit negatively affects cell multiplication and elongation, resulting in reduced photosynthesis and respiration, as well as transpiration and evaporation (TAIZ et al, 2017).…”
Section: Resultsmentioning
confidence: 94%
“…Mineral sources, such as the ammonium sulfate used in the present study, for being more soluble, promote higher N contents in cactus pear cladodes (Silva et al, 2012) and, consequently, greater export of nutrients (Silva et al, 2016a). In addition, the increase in N dose promoted an increase in the concentration and availability of this nutrient in the soil and, consequently, greater export of N (Donato et al, 2017b;Lopes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also shown that cactus pear responds strongly to fertilizer application and irrigation [38,39]. A study conducted in Brazil showed a positive response of cactus pear growth and yield with an increase in N and P fertilization rate up to 130 kg ha −1 N and 190 kg ha −1 P under an annual harvest schedule [18]. Similarly, cactus pear also responds to irrigation, with higher plant growth and yield [40,41].…”
Section: Agronomic Management Practices and Cactus Pear Growthmentioning
confidence: 98%
“…Similarly, cactus pear also responds to irrigation, with higher plant growth and yield [40,41]. The significant response of plant growth and yield to irrigation and fertilizer application may be due to higher capacity to produce biomass per unit time [18,42]. The lack of effect of agronomic management on plant height, cladode number, cladode weight and biomass yield could be due to several other factors such as plant character, acclimatization ability in a new environment and genotype genetic potential.…”
Section: Agronomic Management Practices and Cactus Pear Growthmentioning
confidence: 99%
See 1 more Smart Citation